Success factors of traditional food product of small medium enterprise (SMEs) based on tourist satisfaction in Bandar Hilir, Melaka / Nur Ainna Aznida Abdullah, Nur Shahirah Aziz and Nuratiqa Hidayat Ahmad Jafni - Abdullah, Nur Ainna Aznida; Aziz, Nur Shahirah; Ahmad Jafni, Nuratiqa Hidayat (2015)
This study seeks to identify the critical success factors and the effect of traditional food product of Small Medium Enterprises (SMEs) towards tourist satisfaction in Banda Hilir, Melaka. The study examined three factors that influenced the success factor of SMEs. These factors are; service quality (SERVQUAL Dimension), food quality and customer perceived value (Price). The theoretical framework has been drawn out and questionnaire was design based on the factors chosen. The data collected were analyzed by using SPSS program, which provides relevant analysis such as reliability analysis, frequency analysis, and descriptive analysis. The result conveys that the main success factor of the traditional foods SMEs is customer perceived value (price).